2019
DOI: 10.1155/2019/4604132
|View full text |Cite
|
Sign up to set email alerts
|

Structural Performance of Translucent Concrete Façade Panels

Abstract: Energy conservation is an emerging global issue for sustainable infrastructure development. The building sector energy demand accounts for approximately 34% of the world’s energy demand, and artificial lighting consumes around 19% of the total delivered electricity globally. Developing a new kind of building material that can reduce the demand for artificial lighting energy is vital. This research attempts to address such issues through the development of translucent concrete façade using locally available mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Further research has shown that the amount of light that optical fibers are able to transmit is significantly greater than that of plastic pipes or rods [23]. The above-mentioned elements allow for the transmission of the entire light spectrum, including the transmission of infrared radiation, which provides heat losses and gains [24]. One of the most famous and spectacular structures using light-transmitting concrete is the Italian Pavilion for EXPO 2010 in Shanghai.…”
Section: Theory Of Light-transmitting Concretementioning
confidence: 99%
“…Further research has shown that the amount of light that optical fibers are able to transmit is significantly greater than that of plastic pipes or rods [23]. The above-mentioned elements allow for the transmission of the entire light spectrum, including the transmission of infrared radiation, which provides heat losses and gains [24]. One of the most famous and spectacular structures using light-transmitting concrete is the Italian Pavilion for EXPO 2010 in Shanghai.…”
Section: Theory Of Light-transmitting Concretementioning
confidence: 99%
“…This is an important step to endorse LTC as a potential durable unique building material for construction and infrastructure industries. Tuaum et al [64] have kept the centre of attention on LTC facades panels in order to estimate their structural performance. The mechanical properties viz., flexural strength, compressive strength as well as flexural toughness were investigated on LTC manufactured using OF.…”
Section: Mechanical and Physical Propertiesmentioning
confidence: 99%
“…Not merely those examples mentioned earlier, a few potential uses of LTC were also suggested in the literature; however, they are yet to be constructed practically and accepted widely. Besides the use for aesthetic purposes and reducing the light energy consumptions, LTC can also be employed to guarantee safety, security and supervision in infrastructures of banks, prisons and museums too, as suggested by Tuaum et al [64]. The reason behind it is the usual thicker walls of the prisons in the interest to achieve the impact resistance prerequisite, which consequences in a dark atmosphere and depreciates the basic health conditions of the prisoners and serving staff inside.…”
Section: Global Application Of Ltcmentioning
confidence: 99%
“…They discussed about the inclination of the panel and numerical aperture of a POFs or incident angles according to results of their study for the better effectiveness of the LTC. Tuaum et al [10] developed translucent concrete facade with 2%, 4%, and 6% of POFs and evaluated the bulk density along with the compressive and flexural strength. Their experimental results represented that using POFs up to 6% did not affect the bulk density.…”
Section: Introductionmentioning
confidence: 99%